1970
DOI: 10.1002/1097-0142(197009)26:3<680::aid-cncr2820260329>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Paget's disease of the breast

Abstract: Two‐hundred and fourteen cases of histologically proven Paget's disease of the breast were seen at Memorial Hospital during the period 1950 through 1968. Ninety‐six patients were without palpable masses, clinically, and 113 had Paget's disease of the nipple with palpable masses. Two thirds of the patients without palpable masses, clinically, had noninfiltrating carcinoma, and the majority of them had negative nodes in the axilla; accordingly, they have a good prognosis. Ninety percent of the patients with palp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0
6

Year Published

1977
1977
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(98 citation statements)
references
References 2 publications
2
82
0
6
Order By: Relevance
“…The first one is epidermotropic theory which proposes ductal cancer cells have migrated along the basement membrane. The factors MRM modified radical mastectomy, SLNB sentinel lymph node biopsy, ALND axillary lymph node dissection, DCIS ductal carcinoma in situ supporting this hypothesis are immunohistochemistrical correlation of these cells with underlying carcinoma and increased expression of Her-2 in these patients [6,7]. It is proposed that epidermal cells secrete a tropic factor called heregulin-which binds to Her-2 receptor and mobilizes them to the surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one is epidermotropic theory which proposes ductal cancer cells have migrated along the basement membrane. The factors MRM modified radical mastectomy, SLNB sentinel lymph node biopsy, ALND axillary lymph node dissection, DCIS ductal carcinoma in situ supporting this hypothesis are immunohistochemistrical correlation of these cells with underlying carcinoma and increased expression of Her-2 in these patients [6,7]. It is proposed that epidermal cells secrete a tropic factor called heregulin-which binds to Her-2 receptor and mobilizes them to the surface.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of these patients depends on the presence of lump and associated lymph node metastases. They have found that overall survival correlates with lymph node status, with node-negative patients having a survival of 75-95 % whereas in node-positive patients, it was 20-25 % [6,23].…”
Section: Discussionmentioning
confidence: 99%
“…7,20 Evidence supporting the epidermatropic theory is based on studies showing that Paget disease is associated with an underlying breast carcinoma in most patients. 2,4,21,22 Binding of heregulin-a to its receptor on Paget cells can induce chemotaxis of these breast cancer cells, which eventually migrate into the overlying nipple epidermis. 23 It is noteworthy that Paget cells and the underlying associated ductal carcinoma share the same immunohistochemical profile 24 and the same patterns of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,21,22 Although the incidence rates of Paget disease with an underlying tumor decreased steadily between 1988 and 2002, at the same time that mammographic detection of early cancers was improving, the incidence rates of Paget disease without an underlying tumor remained unchanged. Specifically, 227 of 1704 women (13%) with Paget disease had no underlying breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Дол-гое время стандартом лечения РП соска считалась мастэктомия [51,52] с подмышечной лимфодиссек-цией или без нее. Связано это с наличием «скрытых» комплексов рака в удаленной железе, не выявленных на дооперационных обследованиях [29,53].…”
Section: лечение рака педжетаunclassified